Kewarganegaraan dalam Dinamika Politik dan Hukum Islam di Indonesia (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2025)
This consider explores the exchange between citizenship and the flow of political and Islamic law in Indonesia, the world’s biggest Muslim-majority nation with a complex legitimate framework. The essential center of this inquire about is to get it how Islamic values are coordinates into open approach and the national lawful system, and their affect on administrative forms and national identity.Employing a mixed-methods approach, this consider utilizes subjective examination through in-depth interviews with legitimate specialists and policymakers, as well as quantitative examination of later approach information and enactment. Furthermore, the investigate compares the flow in Indonesia with encounters from other nations with blended lawful frameworks, such as Malaysia and Turkey, and investigates the challenges confronted in adjusting Islamic law with human rights.The key discoveries uncover that the integration of Islamic law inside Indonesia's national lawful framework presents both challenges and openings, especially within the domain of social arrangement usage and person rights security. Moreover, the impact of Islamic legislative issues on the authoritative prepare contributes to the arrangement of approaches that reflect devout values. This investigate highlights the require for a adjust between devout standards and human rights, and its suggestions for national character and pluralism in Indonesia.The ponder gives important bits of knowledge for policymakers, scholastics, and lawful professionals in understanding the complex elements between Islamic law and open approach in a multicultural nation. It is expected that this investigate will contribute essentially to endeavors in legitimate change and the advancement of more comprehensive and evenhanded arrangements in Indonesia.